2018
DOI: 10.5606/tftrd.2018.1586
|View full text |Cite
|
Sign up to set email alerts
|

The association of patellar maltracking with infrapatellar fat pad edema and chondromalacia patella: A quantitative morphological magnetic resonance imaging analysis

Abstract: Objectives: This study aims to investigate the relationship of patellofemoral joint morphology with infrapatellar fat pad edema and chondromalacia patella (CP) using patellar maltracking parameters on magnetic resonance imaging (MRI). Patients and methods: Between January 2010 and January 2013, 50 patients with edema in the superolateral portion of the infrapatellar fat pad (the study group) and control group (n=50) with a normal infrapatellar fat pad were identified on MRI to compare with regard to five patel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…We be- Chondromalacia patella is characterized by damage to the knee joint cartilage and leads to instability. In their study, Gürsoy et al reported that the patellar shift in patients with chondromalacia patella and lateral patellofemoral angles was similar to that in patients without chondromalacia patella, whereas trochlear depth was shorter, sulcus angle was wider, and the Insall-Salvati ratio was higher [12]. In the present study, it was found that the prevalence of PTLFCFS increased in patients with chondromalacia patella.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We be- Chondromalacia patella is characterized by damage to the knee joint cartilage and leads to instability. In their study, Gürsoy et al reported that the patellar shift in patients with chondromalacia patella and lateral patellofemoral angles was similar to that in patients without chondromalacia patella, whereas trochlear depth was shorter, sulcus angle was wider, and the Insall-Salvati ratio was higher [12]. In the present study, it was found that the prevalence of PTLFCFS increased in patients with chondromalacia patella.…”
Section: Discussionsupporting
confidence: 66%
“…Matcuk et al and Subhawong et al described that the sulcus angles of patients with PTLFCFS were similar to those of the control group [3,7]. However, Gürsoy et al reported that the sulcus angle was significantly higher in the PTLFCFS group compared with the control group [12]. Widjajahakim et al reported that superolateral Hoffa fat pad edema was not associated with the sulcus angle [9].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In another similar study, a positive correlation was found between ACL tears and patella baja (11). Gursoy et al reported a significant relationship between infrapatellar fat pad edema and chondromalacia patella with patellar maltracking (12). Similarly, Jibri et al demonstrated Şirik, İnan that edema in the superolateral portion of Hoffa's fat pad was associated with patellar maltracking (13).…”
Section: Discussionmentioning
confidence: 84%
“…13 IPFP resection will lead to decreased tibial external rotation, an increase of patellar flexion, and a medialization of the patella. 34 Meanwhile, IPFP edema will influence the patellar maltracking, 27,[35][36][37] indicating the knee malalignment after the change of IPFP volume. In this study, IPFP maximal area showed a significantly positive association with ISR (Table 3).…”
Section: Discussionmentioning
confidence: 99%